2021
DOI: 10.1016/j.jns.2021.119801
|View full text |Cite
|
Sign up to set email alerts
|

Facemask headache: A new nosographic entity among healthcare providers in COVID-19 era

Abstract: MethodsThe study was carried out in patients with dementia who were periodically visited at the CDCD of ASST Spedali Civili. This study took place from April 01 to May 31 2020.Among the information collected: Clinical Dementia Rating Scale, a telephone version of Mini Mental State Examination (Itel-MMSE), the NPI-Q. The Perception of quality of life was investigated by both the caregiver and the patient (EQ5D) and by the Zarit Burden Inventory. ResultsOverall, 90/108 completed the evaluation and the final samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
3
4
1
Order By: Relevance
“…We surveyed 305 Mexican HCWs to investigate the association between PPE use and de novo headaches. The prevalence of de novo PPE-associated headaches in our study was 39.01%, quite similar to the reported prevalence in another studies [7][8][9][10][11] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We surveyed 305 Mexican HCWs to investigate the association between PPE use and de novo headaches. The prevalence of de novo PPE-associated headaches in our study was 39.01%, quite similar to the reported prevalence in another studies [7][8][9][10][11] .…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence of this pandemic healthcare workers (HCWs) were forced to use personal protective equipment (PPE). The prolonged use of PPE has been associated with skin lesions 3 , head and facial discomfort due to heat and humidity, pressure, pain, itching 4,5 , difficulty breathing, fatigue, exertion, 6 and de novo headaches [7][8][9][10][11] . These may negatively impact HCWs' performance and tolerance to long-term use of PPE 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies in different healthcare settings (Back et al, 2020; Díaz‐Agea et al, 2022; Rubinelli et al, 2020), our results confirm that, although facemasks contributed to increase the feeling of safety of blood donation staff at the beginning of the pandemic, their impact on professional tasks and relationship with blood donors is relevant. In line with existing data (Rapisarda et al, 2021), most healthcare professionals in our study reported discomfort and fatigue related to the continuous use of facemasks, with shortness of breath and headache the most mentioned disturbances.…”
Section: Discussionsupporting
confidence: 92%
“…10 This number was similar to the prevalence reported by Köseoğlu Toksoy et al, 11 30.9%. Zaheer et al 12 concluded the prevalence of PPE-associated ECH in Pakistan was 28.2%, identical to the majority in Italy reported by Rapisarda et al, 13 which was 26.50%.…”
Section: Introductionsupporting
confidence: 53%